Esa Sania, Yusran Paris, Fitri: Pengaruh Testimoni Pelanggan Dan Kepercayaan Konsumen Terhadap Keputusan Pembelian Aulia House Cake Kabupaten Luwu - Esa Sania; Yusran Paris; Fitri (BJRM (Bongaya Journal of Research in Management), 2025)
The study aims to analyze the partial and simultaneous effects of customer testimonials and consumer trust on purchasing decisions at Aulia House Cake in Luwu Regency. A quantitative approach was applied involving 78 respondents through a questionnaire and the data were analyzed using multiple linear regression via SPPS version 25. The results show that customer testimonials have a positive and significant effect on purchasing significance of 0,030. Consumer trust also proves to have a poasitive and significant effect with a t-value of 2.847 and a significance of 0.006. The regression coefficients of 0.169 for consumer trust confirm that both simultaneously have a significant effect on purchasing decisions.The findings indicate that an increase in the number of positive testimonials and high levels of consumer trust can driver purchasing customer loyalty through buiding trust and optimizing testimonials-based marketing strategies.Keywords: customer testimonials, consumer trust, purchasing decisionss